Horticultural Therapy to Improve Self-Confidence in the Elderly: Terapi Hortikultura untuk Meningkatkan Rasa Percaya Diri pada Lansia - Qonita, Qonita; Mariyati, Lely Ika (Indonesian Journal on Health Science and Medicine, 2025)
Background: Self-confidence is an essential psychological aspect for the elderly, yet aging often leads to psychosocial challenges, including stress, depression, and reduced social roles. Specific Background: Elderly residents in social institutions frequently experience low confidence, affecting their well-being and social interactions. Knowledge Gap: Although various interventions exist, limited research in Indonesia has investigated horticultural therapy as a structured approach to build elderly self-confidence. Aim: This study examines whether horticultural therapy can significantly improve self-confidence among elderly individuals in Liponsos Sidoarjo. Results: Using a quantitative pre-experimental design with a One Group Pretest-Posttest method, three elderly participants aged 60 and above were observed. Data were collected using a self-confidence scale based on Lauster’s theory and analyzed with Paired Sample T-Test. Findings revealed a significant improvement between pretest and posttest scores (p = 0.048), with a large effect size (Cohen’s d = 2.547). Novelty: Unlike prior studies, this research applied structured gardening activities, from planting to harvesting, within a social institutional context. Implications: Horticultural therapy can serve as a practical and sustainable intervention to enhance psychological well-being and self-confidence in the elderly population of social care facilities. Highlights: Horticultural therapy increased elderly self-confidence Structured gardening activities supported psychological well-being Applicable in social institution settings Keywords: Self-Confidence, Horticultural Therapy, Elderly, Psychological Well-Being, Intervention